2014
DOI: 10.14740/jocmr1777w
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosarcoma of the Proximal Humerus Secondary to Ollier Disease: An 8-Year Follow-Up of Successful Resection of the Tumor With Endoprosthetic Replacement of the Proximal Humerus

Abstract: We present a 25-year-old male patient with a diagnosis of multiple enchondromatosis, who developed chondrosarcoma on the proximal humerus of the right upper limb. The patient had the pre-existing lesions of Ollier’s disease discovered during his childhood. The patient underwent wide resection of the sarcoma with a prosthetic replacement of the proximal humerus. So far we have followed up the patient for 8 years with no evidence of local recurrence and/or metastasis. The therapeutic results have been satisfied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Additionally, if the integrity of the acetabulum is sufficient, bipolar hemiarthroplasty is a better option for patients because the complication rate of this procedure is lower than that of a total hip replacement (4% vs. 22.2%). [ 38 , 39 ] Paul suggested that impending femoral neck lesions should be treated with arthroplasty. [ 34 ] In brief, prostheses are an excellent choice for the treatment of proximal femoral metastases in patients with good general fitness and life expectancy.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Additionally, if the integrity of the acetabulum is sufficient, bipolar hemiarthroplasty is a better option for patients because the complication rate of this procedure is lower than that of a total hip replacement (4% vs. 22.2%). [ 38 , 39 ] Paul suggested that impending femoral neck lesions should be treated with arthroplasty. [ 34 ] In brief, prostheses are an excellent choice for the treatment of proximal femoral metastases in patients with good general fitness and life expectancy.…”
Section: Surgical Managementmentioning
confidence: 99%